Analisis Framing Pemberitaan Salmafina Sunan di Detik.com - Lucinda Reka Putri; Nurul Hasfi (Interaksi Online, 2021)
The phenomenon of religious conversion done by celebrities in 2019 has attracted much online media attention including Detik.com. One of them is the news of Salmafina Sunan which is full of controversy. This research aims to analyze the framing of Salmafina Sunan's religious conversion news by Detik.com. The framing model used in this research is Robert N. Entman's framing model that focused on selecting an issue and bulging the aspect of news. This research used a qualitative method with 30 news from Detik.com from July 10th to August 8th, 2019 as the samples. Based on Entman's framing elements, which are Define Problems, Diagnose Causes, Moral Judgement, and Treatment Recommendation, the findings show that there are four representations for Salmafina, that is (1) Salmafina behaves errant, (2) Salmafina is a disobedient child, (3) Salmafina is problematic, and (4) Salmafina is depressed